Superlubricity of pH-responsive hydrogels in extreme environments - Chau, Allison L.; Getty, Patrick T.; Rhode, Andrew R.; Bates, Christopher M.; Hawker, Craig J.; Pitenis, Angela A. (Frontiers in Chemistry, 2022)
Poly(acrylamide-co-acrylic acid) (P(AAm-co-AA)) hydrogels are highly tunable and pH-responsive materials frequently used in biomedical applications. The swelling behavior and mechanical properties of these gels have been extensively characterized and are thought to be controlled by the protonation state of the acrylic acid (AA) through the regulation of solution pH. However, their tribological properties have been underexplored. Here, we hypothesized that electrostatics and the protonation state of AA would drive the tribological properties of these polyelectrolyte gels. P(AAm-co-AA) hydrogels were prepared with constant acrylamide (AAm) concentration (33 wt%) and varying AA concentration to control the amount of ionizable groups in the gel. The monomer:crosslinker molar ratio (200:1) was kept constant. Hydrogel swelling, stiffness, and friction behavior were studied by systematically varying the acrylic acid (AA) concentration from 0–12 wt% and controlling solution pH (0.35, 7, 13.8) and ionic strength (I = 0 or 0.25 M). The stiffness and friction coefficient of bulk hydrogels were evaluated using a microtribometer and borosilicate glass probes as countersurfaces. The swelling behavior and elastic modulus of these polyelectrolyte hydrogels were highly sensitive to solution pH and poorly predicted the friction coefficient (µ), which decreased with increasing AA concentration. P(AAm-co-AA) hydrogels with the greatest AA concentrations (12 wt%) exhibited superlubricity (µ = 0.005 ± 0.001) when swollen in unbuffered, deionized water (pH = 7, I = 0 M) and 0.5 M NaOH (pH = 13.8, I = 0.25 M) (µ = 0.005 ± 0.002). Friction coefficients generally decreased with increasing AA and increasing solution pH. We postulate that tunable lubricity in P(AAm-co-AA) gels arises from changes in the protonation state of acrylic acid and electrostatic interactions between the probe and hydrogel surface.